PENGARUH TERAPI YOGA TERHADAP KECEMASAN PERAWAT DIERA PANDEMI COVID-19 DI RUMAH SAKIT UMUM BUDI RAHAYU PEKALONGAN - Olivia Nogoelam; Mardi Hartono; Moh. Projo Angkasa; Rahajeng Win Martani (JURNAL LITBANG KOTA PEKALONGAN, 2022)
Background: The increasing number of COVID-19  patients makes many feel anxious and afraid, especially nurses. Yoga is one of the physical exercises that can increase positive endorphin hormones and suppress anxiety so that it makes a person relaxed, calm, and peaceful and can reduce anxiety. Objective: To determine the effect of yoga therapy toward anxiety among nurses during COVID-19  pandemic at Budi Rahayu Pekalongan Hospital. Method: quantitative research with a one-group pretest-posttest experimental research design using questionnaire data collection from respondents' answers. Sampling using a total sampling technique with 60 respondents. Results: The results showed that with the P value of 0.000 <0.05, it can be concluded that there was an effect of yoga therapy on nurse anxiety during the COVID-19  pandemic era at the Budi Rahayu general hospital in Pekalongan. Conclusion: yoga therapy can reduce anxiety in nurses. Keywords: Yoga, anxiety, COVID-19